2022
DOI: 10.1108/tr-08-2022-0389
|View full text |Cite
|
Sign up to set email alerts
|

Tourism and regional carbon emissions: city-level evidence from China

Abstract: Purpose Although extensive studies have examined the link between tourism and carbon emissions, the impact of tourism on carbon emissions remains controversial. In contrast to prior studies, this study aims to investigate the effects of tourism on carbon emissions at the city level and the underlying moderating mechanism. Design/methodology/approach This study designs an econometric model drawing on panel data for 313 city-level regions in China from 2001 to 2019. This study also performs rigorous robustness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Although stakeholders’ ideas and investment models in tourism activities have changed considerably, they actively participated in market competition, injected new vitality into the tourism market, and improved the willingness of tourists to pay [ 63 ]. However, tourist arrivals increase per capita carbon emissions[ 64 ]. Large-scale tourist activities further increase carbon emission [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although stakeholders’ ideas and investment models in tourism activities have changed considerably, they actively participated in market competition, injected new vitality into the tourism market, and improved the willingness of tourists to pay [ 63 ]. However, tourist arrivals increase per capita carbon emissions[ 64 ]. Large-scale tourist activities further increase carbon emission [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, when revealing the spatiotemporal differentiation of carbon emissions from regional tourism in China and its decoupling relationship with tourism economic growth, Xiong [71] found that carbon emissions are significantly increasing as income increases. When discussing the relationship between China's tourism industry and carbon emissions, Zhang [72] found that the number of tourists and tourist income is positively correlated with tourism carbon emissions. In 1999, the standard for the classification and evaluation of the quality of tourism destinations was promulgated and implemented [73], in the following three years, the income and carbon emissions of China's tourism destinations have shown positive growth.…”
Section: Overall Trendmentioning
confidence: 99%